General enterprising tendency (Get) in brazilian taxi drivers: Alternative to unemployment or form of action? (2019)
Advances in information technologies are revolutionizing social relations, including taxi drivers, through software programs. These programs are allowing any driver to transport people, putting taxi drivers in a new position in society and giving them new strategies for making a living. The objective of this paper is to evaluate the degree of entrepreneurship by means of the General Enterprising Tendency model (get) proposed by Caird (1991). The methodology used was quantitative and exploratory, and included the participation of 147 taxi drivers from a taxi cooperative. The results indicate that in none of the constructs analyzed did taxi drivers get the average score to be classified as entrepreneurs; the “need for achievement” construct was the only item that scored farthest from average; and the “autonomy” construct was the closest to the average score. These results suggest that taxi drivers are dedicated to this profession only as an alternative to unemployment. At the same time, it suggests that a public policy for supporting this important actor is required. © 2019, Centro de Estudos de Historia Religiosa. All rights reserved.